A quarta porta do inferno. A vigilância e disciplinamento da luxúria clerical no espaço luso-americano (1640-1750) - Gouveia, Jaime Ricardo (2015)
Structured in seven chapters, this study has a well defined scientific purpose: to study the lustful behaviors of the clergy that, according to Liguori, gives access to the fourth door of Hell, and also to inquire about what mechanisms of monitoring and discipline existed to ban the access of that door, the strategies, the resources, the available agents and structures to reach that aim, and the result of their concrete action in the Luso-American space between 1640 and 1750. Despite the appreciate labor of the Portuguese and Brazilian historiographies in which concerns the ecclesiastic and religious history in the early modern period, the topic of this thesis was never touched deeply with historical sources, particularly using the comparative method. It is not, however, the virginity of the issue, the only reason that explains the option. To search the historical reality through the production of historical knowledge is a process that must be constructed from scientific problems. Thus, there are two main lines of enquiry that structured this thesis in order to argue two ideas that perseverated until know on the historiography. The first one deals with the argument that sees the clergy present on the Atlantic as an uncontrolled group and its lustful evidence as a colonial policy and consequently as a Brazilian exclusivity. According to this theory the endemic dimension of the lustful behaviors of the clergy in Brazil was the result of inoperative and complacent institutions of monitoring, control and discipline. The second one, connected with the first, has to do with the hypothesis of the Inquisition as a “hide- -blame” court which protected lustful clerics. To review both theories constructed in studies not devoted exclusively to the study of the vigilance and control of the clergy’s behavior in the reported spaces it was necessary to look not only to the judicial institutions but also to their interactions with the society, affiliating the study, by this reason, to the religious and ecclesiastical history, in general, and to the social history of the clergy, in particular, considering simultaneously the related politico-institutional, social and intercultural aspects. To do so, this thesis starts with the definition of the lines of enquiry and the units of comparison through the enunciation of questions such as: Which mechanisms of monitoring and discipline of the clergy existed in the Luso-American space? Did these mechanisms have different politics for persecution lustful ecclesiastics in different territories? Could one see colonial Brazil as a “tropic of sins”, as an American exclusivity? Two different politics, two different churches having the lustful evidence in Brazil an intentional political purpose? The majority part of the written and printed sources elected to answer the posed questions have a judicial nature (ecclesiastical and inquisitorial) namely processes, denunciations, pastoral visits, Regiments, Constitutions of the Bishoprics and Archbishoprics, etc., and were crossed, analyzed and criticized in a synchronic and diachronic comparative perspective.